PSPICE MODEL OF THE PV PANEL - Kubba, Zainab M; Samair, Zaid (Al-Nahrain Journal of Science, 2018)
This paper provides theoretical studies of photovoltaic and modeling techniques using equivalent electric circuits. The use of equivalent circuits makes it possible to investigate the characteristics of a PV cell. The method used here is implemented in orcad pspice program. The same modeling technique is also applicable for modeling a PV module. Details are also given of methods of measuring the panel parameters Isc, Rs and Is . Several techniques are described to create new components (PV), in the orcad-pspice simulator library that can be directly called by their equivalent circuits